Pulmonary inflammatory pseudotumor causing lung collapse responding to corticosteroid therapy. (2018) - Reddy, Radhika Z.; Carter, Yvonne M.; Hsia, David W.
Abstract: Pulmonary inflammatory pseudotumor (PIP) is a rare benign tumor that represents less than one percent of all tumors found in the lungs. Despite the benign etiology, PIP can cause significant clinical problems due to its growth rate and potential to compromise adjacent pulmonary and thoracic structures. Complete surgical resection is the preferred therapy for PIP to prevent recurrence, however, this is not possible in some patients due to the size or location of the tumor. We present the case of an 18 year-old male presenting with PIP in the proximal left mainstem bronchus causing complete left lung collapse. Surgical resection was not possible due to tumor location, and therefore the patient was treated with corticosteroids with marked response. Corticosteroid use has for PIP has been described in few other situations, and this case demonstrates the potential for this therapeutic option in patients with PIP who have a contraindication to surgical resection.